The University of Miami Enhanced Recovery After Spine Surgery Program: Update on Outcomes of 311 Consecutive Patients. (16th November 2020) - Borowsky, Peter; Brusko, Gregory D; Huang, Meng; Eliahu, Karen; Wang, Michael Y
Abstract: INTRODUCTION: We have previously characterized initial six-month outcomes of lumbar fusion patients enrolled in a novel Enhanced Recovery After Surgery (ERAS) program. METHODS: A single-institution ERAS protocol has undergone several iterations since inception in March 2018. Current preoperative interventions include nutritional counseling, discharge planning, and carbohydrate loading. Perioperative multimodal analgesia, comprised of gabapentin, liposomal bupivacaine, and intravenous acetaminophen, is currently employed along with minimization of urinary catheters, daily physical therapy, and ERAS rounds postoperatively. In September 2018, a standardized ERAS Care Pathway was implemented in the electronic medical record. Demographic and outcome data was retrospectively collected for ERAS patients prior to September 2018 and prospectively collected following implementation. RESULTS: 311 consecutive patients underwent 1–3 level lumbar fusion. 167 (53.7%) were male. 263 patients (84.6%) were older than 65 years, with 138 older than 75 years. Average length of stay (LOS) was 3.51±3.40 days (median 3.04 days). Twenty-three patients (7.4%) experienced a complication during admission, eight of which were cardiopulmonary and four were related to surgery. One patient required reoperation during admission due to hematoma formation. Six patients (1.9%) were readmitted within 30 days, including two who returned to the emergency room within seven days of discharge. 245 patients (78.8%) were discharged home compared to rehab. Average time to ambulation following surgery was 25.7±18.2 hours, with patients increasing ambulation distance 86.8±154.1 feet from first to last physical therapy visit. The maximum amount of daily morphine equivalents (ME), on average, was 21.2±34.3, with an average decrease from first to last ME amount of 30.6±32.0. CONCLUSION: This is the largest known series examining patients undergoing lumbar fusion within an iterative ERAS program. Patients, on average, experienced both a short hospital LOS and low readmission rate supporting the utility of our ERAS pathway to reduce LOS without increasing readmissions.